ADQUISICIONES RECIENTES SOBRE VIRUS (CON) RECENT DEVELOPMENTS ON VIRUSES - TAFALL OSORIO, B F (Instituto Politécnico Nacional, CD MEXICO, DF, MEX, 1948)
In the rabbit, hyaluronidase from purified testicular extract increased the spread areas of injected India ink 6 times over those of the controls Admn of Na salicylate inhibited the spreading effect of hyaluronidase but sulfadiazine did not The signif
CIENC MEX
Keywords: ADQUISICIONES, VIRUS; MULTIDISCIPLINARIA; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); VIROLOGIA MEDICA